Peran Media Pembelajaran Digital dalam Pembelajaran Matematika di Era Merdeka Belajar : Systematic Literature Review (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This article aims to examine the role of digital learning media in supporting mathematics learning that is aligned with the spirit of the Merdeka Curriculum. The research was conducted using the Systematic Literature Review (SLR) method on twenty scientific articles that discuss the use of digital media in learning mathematics at various levels of education. The results of the study show that digital learning media such as the Canva application, Wordwall, digital comics, animated videos, and educational games can significantly improve concept understanding, learning motivation, and student engagement. Digital media also supports the differentiated and contextual learning approach that is the main characteristic of Merdeka Curriculum. This study concludes that digital media is not only effective in conveying abstract material visually and interactively, but also encourages the development of students' 21st century skills, such as critical thinking, independence, and creativity. The findings are expected to be a reference for teachers, researchers, and policy makers in designing innovative and adaptive mathematics learning strategies in the digital era.